The Effectiveness Of Telehealth In Nursing Practice In KSA: A Systematic Review Of Recent Studies (Journal of Namibian Studies : History Politics Culture, 2023)
Background. Telemedicine in Saudi Arabia is transforming nursing practice, enabling nurses to provide timely, efficient care to patients across vast geographical areas. This technology facilitates remote consultations, patient monitoring, education, and surgical assistance, aligning with the country's vision for a modern, technology-driven healthcare system. As telemedicine continues to evolve, it is poised to play a crucial role in enhancing healthcare delivery and patient outcomes. The aim of current systematic review is to see the effectiveness of telehealth in nursing practices in KSA. Method. Scopus, PsycINFO, and Web of Science were used to categorize research published between 2020 and 2024 on evaluating the effectiveness of telehealth in nursing practices in KSA. After screening and quality evaluation, eleven studies were included in the synthesis, focusing on team dynamics and measurement scales.Result. After the study database was searched, 2021 entries were found, and 12 of them were chosen for full-text evaluation. Twelve studies that used quality management and peer-reviewed journals satisfied the criteria and were added to the systematic review following independent evaluation. The studies identified sub-themes including knowledge, attitudes, perceptions, barriers to telemedicine adoption, COVID-19 pandemic role, teleophthalmology, nursing interventions, nursing workforce competencies, job satisfaction, awareness, and reducing emergency department overload. Conclusion. According to the results of the studies included in this systematic review that Saudi Arabian telemedicine and telehealth research reveals the potential benefits and drawbacks of these technologies in healthcare. While telehealth can improve patient outcomes and treatment access, challenges such as lack of knowledge, data security concerns, and interoperability need to be addressed. The COVID-19 pandemic has highlighted the importance of telemedicine in preserving healthcare access. However, further infrastructure and training investments are needed to maximize its efficacy. The study suggests that Saudi Arabian healthcare workers, including nurses, need adequate training in telehealth technology to improve healthcare delivery, manage chronic illnesses, and provide personalized care. Recommendations include funding extensive training programs, addressing infrastructural issues, establishing regulatory frameworks, promoting equity, integrating telehealth into nursing curricula, fostering collaboration, and implementing continuous evaluation and quality improvement measures.